1982
DOI: 10.1177/002221948201501002
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse: Growth Failure, IQ Deficit, and Learning Disability

Abstract: Behavior that has been criminalized makes criminals not only of those who practice it but also of professionals who fail to report their knowledge of it. Professionals have invented the bastard science of victimology in which, by focusing on the victims and handing the offenders over to the law, they miss the scientific opportunity to discover the cause and prevention of the offense. Evidence of child abuse and neglect as a primary cause of permanent IQ impairment and learning disability, though long known, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The association of ACEs and body weight abnormalities could be explained by the development of a thrifty phenotype under the influence of adverse life events [ 41 ].The thrifty phenotype leads to changes in the child's metabolism [ 42 ], which are related with reduced energy expenditure [ 43 ], but also with greater susceptibility to the consumption of large amounts of food [ 44 ]. Overeating can be fostered by hormonal changes under the influence of stressors [ 45 ], among others.…”
Section: Discussionmentioning
confidence: 99%
“…The association of ACEs and body weight abnormalities could be explained by the development of a thrifty phenotype under the influence of adverse life events [ 41 ].The thrifty phenotype leads to changes in the child's metabolism [ 42 ], which are related with reduced energy expenditure [ 43 ], but also with greater susceptibility to the consumption of large amounts of food [ 44 ]. Overeating can be fostered by hormonal changes under the influence of stressors [ 45 ], among others.…”
Section: Discussionmentioning
confidence: 99%
“…Family violence is considered a significant public health problem (Burke, O'Campo & Peak, ; Di Bartolo, ). Family violence victims are more likely to be currently in poor health, to have depressive symptoms, to be involved in substance abuse, and to develop chronic diseases and chronic mental illnesses (Coker et al., ; Cunradi, Caetano, Clark & Schafer, ; Koenig, Ahmed, Hossain & Mozumder, ; Money, ; World Health Organization, 2002). These outcomes devastate both the individual victims and society in general because family violence exhausts the resources of employers and of public and voluntary services (O'Campo et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the literature on abuse of people with disabilities has focused on children (Diamond & Jaudes, 1983;Frisch & Rhoads, 1982;Green, Voeller, Gaines & Kubie, 1981;Money, 1982;Murphy, 1982;Nesbit, & Karagiania, 1982;Rose & Hardman, 198 1 ;Soeffing, 1975;Sandgrund, Gaines, & Green, 1974;Solomons, 1979;Starr, Dietrich, Fischhoff, Ceresnie, & Zwier, 1984;Valentine, 1990;Zirpoli, 1986;Zirpoli, 1990). These studies indicated that mental retardation may be a cause and an effect of child abuse.…”
mentioning
confidence: 99%